The role of Transport Logistics in Promoting Algeria’s Economic Growth: Econometric Study for the period 1990-2021 - Bachouche Hayet; Tahraoui Farid (Journal of North African Economies, 2025)
This study examines the role of transportation logistics in promoting economic growth in Algeria during the period 1990-2021, using the Autoregressive Distributed Lag (ARDL) model. The study employs data on the volume of goods transported by sea, air, road, and rail as logistics indicators, while Gross Domestic Product (GDP) serves as an indicator of economic growth. The results obtained indicate a long-term positive relationship between transportation logistics and economic growth. The results obtained indicate a positive relationship in both short and long terms between transportation logistics and economic growth. The Toda-Yamamoto causality test suggests that transportation logistics does not impact economic growth, and vice versa. Based on the proposed model, it can be concluded that logistics services play a significant role in enhancing economic growth in Algeria.